Pretracheal Lymph Node Subdivision in Predicting Contralateral Central Lymph Node Metastasis for Unilateral Papillary Thyroid Carcinoma: Preliminary Results - Chen, Qiang; Liu, Yang; Lu, Wei; Zhang, Lingyun; Su, Anping; Liu, Feng; Zhu, Jingqiang (Frontiers in Endocrinology, 2022)
Background: The aims of this study were to assess the clinical value of pretracheal lymph nodes (LNs) subdivision in identifying patients with contralateral central lymph node metastasis (CLNM) and risk factors of occult contralateral CLNM in unilateral PTC. Methods: A total of 139 unilateral PTC patients with clinically node-negative neck (cN0) who underwent bilateral central neck dissection (CND) were prospectively enrolled. Intraoperatively, pretracheal region was further divided into ipsilateral and contralateral subregions. Ipsilateral and contralateral pretracheal LNs as well as other CLNs (prelaryngeal, ipsilateral paratracheal and contralateral paratracheal) were labeled separately and sent for pathological examination. Demographic and clinicopathologic variables were analyzed to identify factors predictive of contralateral CLNM. Results: Of 139 patients, bilateral CLNM was present in 37 (26.6%) patients. Contralateral pretracheal LNM was significantly associated with contralateral CLNM. In multivariate analysis, prelaryngeal LNM (P = 0.004, odds ratio = 3.457) and contralateral pretracheal LNM (P = 0.006, odds ratio = 3.362) were identified as risk factors of contralateral CLNM. Neither neck recurrence nor distant metastasis occurred within the mean follow-up period of 9.1 ± 1.8 months. Conclusions: In most unilateral cN0 PTCs, ipsilateral CND is adequate, while patients presenting with evident nodal disease intraoperatively or preoperatively in the contralateral central neck should undergo bilateral CND. Intraoperative re-evaluation of prelaryngeal and contralateral pretracheal LNs may be helpful in determining the extent of CND.